Preaching Death : The Transformation of Christian Funeral Sermons - Bregman, Lucy (Book collections on Project MUSE., 2011)
Christians traditionally have had something substantive and important to say about death and afterlife. Yet the language and imagery used in sermons about life and death have given way to language designed to comfort and celebrate. In Preaching Death, Lucy Bregman tracks the changes in Protestant American funerals over the last one hundred years. Early-twentieth-century "natural immortality" doctrinal funeral sermons transitioned to an era of "silence and denial," eventually becoming expressive, biographical tributes to the deceased. The contemporary death awareness movement, with the "death as a natural event" perspective, has widely impacted American culture, affecting health care, education, and psychotherapy and creating new professions such as hospice nurse and grief counselor. Bregman questions whether this transition--which occurred unobserved and without conflict--was inevitable and what alternative paths could have been chosen. In tracing this unique story, she reveals how Americans' comprehension of death shifted in the last century--and why we must find ways to move beyond it. -- Publisher.